The Status of Freshwater Mussels (Unionidae) of Virginia - Michael L. Lipford (Hello World!, 1989)
The Virginia Natural Heritage Program (VANHP) was established through the joint efforts of The Nature Conservancy and the Commonwealth of Virginia. The VANHP, through inventory technique, maintains a continuously updated database that reflects the current status of biological diversity in Virginia.